Diagnosis of tularemia using piezoelectric biosensor technology - Pohanka, Miroslav; Pavlis, Oto; Skládal, Petr (Talanta, 2007)
A piezoelectric immunosensor for indirect diagnosis of tularemic infection in mouse serum was developed. Francisella tularensis LVS antigen was covalently immobilized on the sensing surface using cystamine and glutaraldehyde for activation and modification of the gold electrode. The normal mouse serum (NMS) and serum prepared from mice immunized by Escherichia coli were used as negative controls providing signal of 28Hz during a 5min interaction. The tularemic infectious (immunized) mouse serum (IMS) as sample resulted in the signal above 75Hz (fifth day after infection). The control sensor containing bovine serum albumin as sensing element provided a signal below 5Hz with NMS as well IMS. The effects of dilution degree and purification of sera were tested. To improve resolution of the method, sample pretreatment steps such as precipitation with ammonium sulphate and immunoglobulin extraction on CBind L and MEP HyperCel columns were tested. R.S.D. of measurements was 2.3% for NMS and 2.4% for IMS, respectively. The developed method allows to indicate the presence of anti-tularemic antibodies shortly (1-3 days) after infection, one analysis is completed in 10min.